2006
DOI: 10.1093/alcalc/agl033
|View full text |Cite
|
Sign up to set email alerts
|

Liver Transplantation for Alcoholic Liver Disease: A Systematic Review of Psychosocial Selection Criteria

Abstract: Social stability, no close relatives with an alcohol problem, older age, no repeated alcohol-treatment failures, good compliance with medical care, no current polydrug misuse, and no co-existing severe mental disorder have all been associated with future abstinence in more studies than not, in those that examined these variables. Duration of preoperative abstinence was a poor predictor. We recommend that, if predicting future abstinence is considered necessary by transplant teams, a standardized approach is ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
69
0
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(80 citation statements)
references
References 25 publications
4
69
0
7
Order By: Relevance
“…The authors showed that although pre-OLT abstinence duration was a predictor on the frequency as well as time to relapse to alcohol abuse after OLT, even in patients who were sober for 36 mo, only 40% remained sober after OLT [13] . The lack of correlation of post-OLT recidivism with 6 mo abstinence prior to OLT was also shown by McCallum et al [14] in their systematic review of 11 studies. Only 2 of the studies showed an association while 9 studies did not show an association between 6 mo pre-OLT abstinence and post-OLT recidivism [14] .…”
Section: Ethical Concerns and Issuesmentioning
confidence: 59%
See 4 more Smart Citations
“…The authors showed that although pre-OLT abstinence duration was a predictor on the frequency as well as time to relapse to alcohol abuse after OLT, even in patients who were sober for 36 mo, only 40% remained sober after OLT [13] . The lack of correlation of post-OLT recidivism with 6 mo abstinence prior to OLT was also shown by McCallum et al [14] in their systematic review of 11 studies. Only 2 of the studies showed an association while 9 studies did not show an association between 6 mo pre-OLT abstinence and post-OLT recidivism [14] .…”
Section: Ethical Concerns and Issuesmentioning
confidence: 59%
“…The lack of correlation of post-OLT recidivism with 6 mo abstinence prior to OLT was also shown by McCallum et al [14] in their systematic review of 11 studies. Only 2 of the studies showed an association while 9 studies did not show an association between 6 mo pre-OLT abstinence and post-OLT recidivism [14] . Does this mean that recidivism after OLT is not important?…”
Section: Ethical Concerns and Issuesmentioning
confidence: 59%
See 3 more Smart Citations